Proceso de atención de enfermería en paciente de 20 años con bajo peso preconcepcional. - Toro Arboleda, Karla Zuliana (2020)
During pregnancy physiological, hormonal and biochemical changes occur that influence the woman's need for nutrients; These changes are necessary for fetal development and growth, maternal maintenance during pregnancy and preparation of the mother for childbirth and lactation, which is why the woman must reach this period in the best possible nutritional conditions. Inadequate nutrition is a serious health problem worldwide that brings with it innumerable disorders, the gestational period is one of the most critical in this regard and is not exempt from adverse results for the health of the mother, fetus and the newborn; For this reason, we set out to carry out this study in order to determine the perinatal results in pregnant women with low pregestational weight in a 20-year-old patient.